Engineering ZnO nanowire surfaces via a chemical method. Issue 12 (28th July 2014) - Zhu, Y. F.; Fan, D. H.; Zhou, G. H.; Gu, F.
<x xml:space="preserve">Abstract</x> Porous nanowires with large surface area are advantageous for device applications. However, the synthesis of this kind of nanostructure has rarely been reported. In this paper, quasi‐aligned ZnO nanowire arrays with porous surfaces were successfully fabricated via a facile chemical method. Time‐dependent experiments have also been carried out to better understand the formation process of porous structure on the nanowire surface. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>